The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4137/ccrpm.s12178
|View full text |Cite
|
Sign up to set email alerts
|

Use of Noninvasive Gas Exchange to Track pulmonary Vascular Responses to exercise in Heart Failure

Abstract: We determined whether a non-invasive gas exchange based estimate of pulmonary vascular (PV) capacitance [PVCAP = stroke volume (SV) × pulmonary arterial pressure (Ppa)] (GXCAP) tracked the PV response to exercise in heart-failure (HF) patients. Pulmonary wedge pressure (Ppw), Ppa, PV resistance (PVR), and gas exchange were measured simultaneously during cycle exercise in 42 HF patients undergoing right-heart catheterization. During exercise, PETCO2 and VE/VCO2 were related to each other (r = −0.93, P < 0.01) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(64 citation statements)
references
References 25 publications
3
60
1
Order By: Relevance
“…Patients with chronic HF commonly exhibit an excessive ventilatory response to exercise (12, 17) and experience significant derangements in pulmonary gas exchange at rest and during exercise (1013, 18). Previously, we have shown that the frequently observed increase in V D /V T and V̇ E /V̇CO 2 during exercise in HF is due, at least in part, to a relative hyperventilation and a rapid and shallow breathing pattern (12), both of which are likely related to a reduction in lung compliance secondary to pulmonary congestion (19) and/or cardiomegaly (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with chronic HF commonly exhibit an excessive ventilatory response to exercise (12, 17) and experience significant derangements in pulmonary gas exchange at rest and during exercise (1013, 18). Previously, we have shown that the frequently observed increase in V D /V T and V̇ E /V̇CO 2 during exercise in HF is due, at least in part, to a relative hyperventilation and a rapid and shallow breathing pattern (12), both of which are likely related to a reduction in lung compliance secondary to pulmonary congestion (19) and/or cardiomegaly (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is becoming increasingly clear that the progressive deterioration in pulmonary vascular function and the occurrence of PH in HF is not only associated with exercise intolerance (3, 21) but also further exacerbates pulmonary gas exchange abnormalities in these patients. For example, we have shown that V̇ E /V̇CO 2 and PETCO 2 are both significantly related to invasively determined mPAP during submaximal exercise in HF patients, and that V̇ E /V̇CO 2 was greater and PETCO 2 lower during exercise in HF patients with PH compared to HF patients without PH, although the difference in PETCO 2 did not reach statistical significance (13). In addition, Guazzi et al (15) reported that a V̇ E /V̇CO 2 slope ≥ 36 and, to a lesser extent, a peak PETCO 2 ≤ 34 mmHg and the presence of oscillatory ventilation in response to exercise were excellent predictors of the presence of left sided PH in HF patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Circulatory power (CircP) is a robust non-invasive surrogate for cardiac power that is also indicative of prognosis in HF (5, 39). We have also recently shown that oxygen pulse (O 2 pulse) during exercise strongly correlates with invasive measurements of SV in HF patients with or without secondary PH (36). Equally important, end-tidal partial pressure of CO 2 (P ET CO 2 ) is related to changes in pulmonary vascular pressures during exercise in HF (36).…”
Section: Introductionmentioning
confidence: 96%
“…Although the pathophysiology of secondary PH in HF remains incompletely understood, it is likely that augmented pulmonary vascular pressures first occur because of passive downstream increases in left heart pressures due to ventricular dysfunction (3, 4, 23), which later transgresses to a mixed form of PH related to vascular remodeling resulting in persistently elevated pulmonary vascular resistance (3, 4, 23). Exercise further exacerbates elevations in pulmonary vascular pressures in HF patients with secondary PH (4, 36). Therefore, because an ample body of evidence suggests that exercise measurements of both cardiac and pulmonary system function are clear markers of syndrome severity and prognosis in HF (4, 10, 18-20), it is necessary to study potential pathophysiological mechanisms contributing to changes in pulmonary pressures in HF during a paradigm that includes rest and exercise testing.…”
Section: Introductionmentioning
confidence: 99%